Dispute Resolution And Dynamics Of Legal Aspects In Sharia Banking Practices In Indonesia - Muhammad Zuhdi Asyrofi; Muhammad Albahi; Raja Sakti Putra Harahap (LP2M IAIN Palopo, 2026)
This study aims to analyze the dispute resolution mechanisms and the dynamics of legal aspects in Islamic banking practices in Indonesia. The background of this research is based on the rapid development of the Islamic banking industry accompanied by an increasing potential for disputes due to default, differences in contract interpretation, and violations of Islamic principles. This study uses a qualitative approach with a normative (doctrinal) research type through a library study of laws and regulations, legal literature, and court decisions. The results show that Islamic banking disputes have unique characteristics that are not only contractual, but also contain normative-religious dimensions because they must meet the principles of Islamic compliance. Dispute resolution can be achieved through two channels: non-litigation (negotiation, mediation, and Islamic arbitration) which emphasizes the principles of deliberation and substantive justice, and litigation through the Religious Courts which provides legal certainty. In addition, the dynamics of legal aspects in Islamic banking practices indicate challenges in the form of legal pluralism, regulatory disharmony, and the development of Islamic financial technology that requires legal adaptation. Thus, it is necessary to harmonize positive law and sharia principles as well as increase the capacity of law enforcement agencies in order to create a dispute resolution system that is effective, fair and provides legal certainty for the parties.